Antithyroid Antibody Status During Pregnancy - Banik, Shyamal Chandra; Alo, Kamrunnahar; Ahmed, Farjana; Islam, Najmul; Towhid, Ferdous (KYAMC Journal, 2021)
Background: Gradual alteration of antithyroid antibody level occurs during different trimesters of gestation. The study finds the type of alteration in Bangladeshi population. Objective: The present study was carried out to find out the alterations of antithyroid antibody levels during each trimester in normal pregnant women in Bangladesh. Materials and Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from July 2016 to June 2017. Total 90 apparently healthy pregnant women of different trimesters, age ranged from 20 to 35 years were selected as study group (Group I). Again according to gestational age, study group was subdivided into 1st trimester of gestation (Group Ia, n=30), 2nd trimester of gestation (Group Ib, n=30) and 3rd trimester of gestation (Group Ic, n=30) respectively for comparison. For assessment of antithyroid antibody status, serum TPO-Ab and Tg-Ab levels were measured by chemiluminescent microparticle immunoassay (CMIA) method in Bangabandhu Sheikh Mujib Medical University (BSMMU). The statistical analysis was done by ANOVA test and Bonferroni test. Results: In this study, mean serum TPO-Ab level was significantly (p≤0.05, p<0.001) lower in 2nd and 3rd trimester in comparison to that of 1st trimester. On the other hand, mean serum Tg-Ab level was significantly (p<0.01, p<0.001) lower in 2nd and 3rd trimester in comparison to that of 1st trimester. Again, this value was significantly (p≤0.05) lower in 3rd trimester than that of 2nd trimester. Conclusion: Antithyroid antibody titre gradually decreases with the progression of trimesters of gestation. KYAMC Journal.2021;12(02): 98-100